Flow velocity sensors arrangement for vegetated channels - Zhou, Yi; Yao, Weiwei; He, Xiangli; Li, Tongshu; Wang, Shiyu; Han, Yu (Frontiers in Plant Science, 2022)
Ecological rivers or ecological channels are being widely used. Precious measurement and estimation of flow in irrigation areas are important issues in agricultural engineering. For the sustainable development of vegetation, it is necessary to consider how to use sensors to measure flow more easily in the river to protect both plants and sensors from damage. This article selects smooth channels and ecological channels of different shapes for research and presents a simplified method for arming ultrasonic sensors to obtain channel flow velocity. The flow characteristics along the normal line direction are obtained by theoretical analysis. The method uses the average flow velocity based on the normal to the channel wall to determine the location of the sensors. It combines the flow velocity determined by the sensors with the flow calculation method, thus simplifying the flow estimation steps. Experiments under flow conditions validate the efficacy of the proposed ultrasonic sensor arrangement method. This article not only simplifies the arrangement of sensors in channel flow but also improves the accuracy of the flow measurement method, which is important to promote the construction of ecological channels.